2013
DOI: 10.1002/rcm.6745
|View full text |Cite
|
Sign up to set email alerts
|

Unleashing radical sites in non‐covalent complexes: The case of the protonated S‐nitrosocysteine/18‐crown‐6 complex

Abstract: Cleavage of the weak S-NO bond has allowed the formation of a radical site onto a non-covalent complex. Ion-molecule reactions and collisional activation were utilized to probe the chemistry of this radical cation. The approach adopted here for incorporating a radical onto a cysteine/crown complex shows promise for the introduction of radical sites onto other biological non-covalent complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Each of the amine thiols (2-amino-1-ethanethiol; 3-amino-1-propanethiol, and 4-amino-1-butanethiol) were separately nitrosylated in 1:1 methanol–water solution with tert -butyl nitrite as described previously. The resultant reaction solutions containing the S -nitrosoamines were diluted to a 0.5 mM 1:1 methanol–water solution and directly infused into the electrospray ionization (ESI) source of a modified hybrid LTQ FT-ICR mass spectrometer at a flow rate of 5.0 μL min –1 . In the positive ion mode, the S -nitrosoammonium ions, H 3 N + (CH 2 ) n SNO were formed and the source conditions were tuned to optimize their signal.…”
Section: Experimental and Theoretical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of the amine thiols (2-amino-1-ethanethiol; 3-amino-1-propanethiol, and 4-amino-1-butanethiol) were separately nitrosylated in 1:1 methanol–water solution with tert -butyl nitrite as described previously. The resultant reaction solutions containing the S -nitrosoamines were diluted to a 0.5 mM 1:1 methanol–water solution and directly infused into the electrospray ionization (ESI) source of a modified hybrid LTQ FT-ICR mass spectrometer at a flow rate of 5.0 μL min –1 . In the positive ion mode, the S -nitrosoammonium ions, H 3 N + (CH 2 ) n SNO were formed and the source conditions were tuned to optimize their signal.…”
Section: Experimental and Theoretical Methodsmentioning
confidence: 99%
“…For example, intramolecular hydrogen bonding of the side chains of serine and threonine constrains free radical reaction dynamics at these residues . As part of a series of studies on the structure and reactivity of thiyl distonic ions derived from cysteine, its derivatives, and peptides, we discovered that the thiyl radical of cysteine, 1a (Scheme ), is more reactive with respect to atom abstraction reactions than homocysteine, 1b . We speculated that this may be due to differences in the strength of intramolecular hydrogen bonding …”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that all three requirements can indeed be met [19]. As a "proof of concept", the non-covalent complex between protonated S-nitrosocysteine and 18-crown-6 (18-C-6) was formed by ESI and shown to fragment via NO loss to produce the radical cation non-covalent complex (Eq.…”
Section: Introductionmentioning
confidence: 98%
“…Inspired by Nature"s use of enzyme radical chemistry to biocatalytically transform carbohydrate-based substrates [25][26][27][28][29][30][31], we have previously described an approach that utilizes a charged non-covalent complex between a sugar and a radical to generate a charged sugar radical [32,33]. The method (Scheme 1) involves: (i) transfer to the gas phase of a charged non-covalent complex containing a sugar and a radical precursor (an Snitrosoamine); (ii) formation of the radical cation non-covalent complex by unleashing the radical site from the precursor in preference to dissociation of the non-covalent complex (step (a) of Scheme 1); and (iii) transfer of both the radical and charge sites to the sugar upon dissociation of the radical cation non-covalent complex (step (b) of Scheme 1).…”
Section: Introductionmentioning
confidence: 99%